A level-set based continuous scanning path optimization method for reducing residual stress and deformation in metal additive manufacturing - Chen, Qian; Liu, Jikai; Liang, Xuan; To, Albert C. (Computer methods in applied mechanics and engineering, 2020)
Thermal residual stress and distortion inherent in metal melting and solidification process is the main cause of build failure in metal additive manufacturing (AM) techniques such as laser powder bed fusion and directed energy deposition. To ensure build quality against residual stress/distortion, it is desirable to tailor the scanning path for a given geometry that needs to be built. Since the local deformation introduced by the moving heat source is anisotropic due to non-uniform heat transfer and mechanical constraints, the scanning path can affect residual stress within a part significantly. Aiming at thermal residual stress/distortion mitigation, this paper presents a novel level set-based scanning path optimization method. The method is developed to enable layer-wise continuous scanning path optimization for geometrically well-defined parts. To make the optimization efficient, a fast process simulation method called the inherent strain method is employed to simulate the thermal residual strain. Full sensitivity analysis for the formulated compliance- and stress-minimization problems is provided, where a novel strategy called the adaptive level set adjustment (ALSA) is proposed to remedy the deficiency of ignoring the non-implementable sensitivity terms. The effectiveness of the proposed continuous scanning path optimization method and ALSA strategy has been proved by a few numerical examples. Finally, the concurrent design scenario for simultaneous scanning path and structural optimization is investigated to demonstrate the further residual stress reduction.